2017
DOI: 10.1007/s00414-017-1627-1
|View full text |Cite
|
Sign up to set email alerts
|

DNA persistence of bite marks on food and its relevance for STR typing

Abstract: In forensic DNA analysis, salivary traces at crime scenes are a promising way to identify a person. However, crime scenes are oftentimes investigated a while after the crime and recovered samples might have been degraded leading to poor PCR amplification. Probably due to decomposition and negative visual impression of spoiled food, bite mark samples make up only a small part of our casework routine. In this study, bite marks on apples and chocolate bars as well as on an inert surface (microscope slide) were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Unfortunately, bite marks are rarely swabbed and sampled for DNA analysis. Pfeifer et al [ 131 ] examined bite marks on apples and chocolate bars and proved that STR analysis is possible after 21 days, even in samples collected from moldy fruit. Mold reduced the amount of amplifiable DNA but did not rule out a successful STR analysis [ 131 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, bite marks are rarely swabbed and sampled for DNA analysis. Pfeifer et al [ 131 ] examined bite marks on apples and chocolate bars and proved that STR analysis is possible after 21 days, even in samples collected from moldy fruit. Mold reduced the amount of amplifiable DNA but did not rule out a successful STR analysis [ 131 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
“…Pfeifer et al [ 131 ] examined bite marks on apples and chocolate bars and proved that STR analysis is possible after 21 days, even in samples collected from moldy fruit. Mold reduced the amount of amplifiable DNA but did not rule out a successful STR analysis [ 131 ]. Earlier studies indicated that saliva DNA could be preserved on bite marks for 16 [ 132 ] and 24 h [ 133 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
“…A study of recovery of STR profiles from bite marks underlined the stability of human nuclear DNA not only on inert surfaces but also on biological surfaces and their forensic usefulness even when bite marks are stored 21 days under adverse but realistic conditions at a crime scene [ 126 ]. Whether it was possible to distinguish social contact from sexual activity was considered by searching for female profiles on the inside of male underpants [ 127 ].…”
Section: Dna Transfer and Activity Level Evaluationsmentioning
confidence: 99%
“…While several studies deal with the possibilities of DNA transfer [e.g., [6][7][8][9], studies on the persistence of DNA are still rare and have mostly been conducted under laboratory conditions [10][11][12][13]. Investigations of outdoor scenarios are mainly limited to restricted conditions [14][15][16][17][18][19]. Especially, the influence of weather on DNA stability is a very rare topic.…”
Section: Introductionmentioning
confidence: 99%